2019
DOI: 10.1002/aet2.10372
|View full text |Cite
|
Sign up to set email alerts
|

The Equivalence of Video Self‐review Versus Debriefing After Simulation: Can Faculty Resources Be Reallocated?

Abstract: Introduction: Traditional simulation debriefing is both time-and resource-intensive. Shifting the degree of primary learning responsibility from the faculty to the learner through self-guided learning has received greater attention as a means of reducing this resource intensity. The aim of the study was to determine if video-assisted self-debriefing, as a form of self-guided learning, would have equivalent learning outcomes compared to standard debriefing.Methods: This randomized cohort study consisting of 49 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Learners preferred debriefing that focused on specific actions versus debriefing that focused on thought processes (reaction SMD = 0.55, n = 62 participants) 54 . Another study found that performance improved with video self‐debriefing compared to traditional debriefing by faculty (non–time skills SMD = 0.21, n = 49 participants) 55 …”
Section: Resultsmentioning
confidence: 99%
“…Learners preferred debriefing that focused on specific actions versus debriefing that focused on thought processes (reaction SMD = 0.55, n = 62 participants) 54 . Another study found that performance improved with video self‐debriefing compared to traditional debriefing by faculty (non–time skills SMD = 0.21, n = 49 participants) 55 …”
Section: Resultsmentioning
confidence: 99%
“…The traditional model for simulation-based training includes post-simulation feedback in which students’ experiences are discussed and reflected upon to improve future performance [ 18 ]. A better understanding of the role of feedback in competency-based education could result in a more efficient learning process for the trainees [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the traditional model, an expert is needed for the post-simulation feedback session. Transitioning the primary responsibility from an expert to the trainee’s self through self-guided learning has received increasing attention, mainly due to the potential of reducing the resources needed [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional model for simulation-based training includes post-simulation feedback in which students' experiences are explored and re ected upon to improve future performance (17). A better understanding of the role of feedback in competency-based education could result in a more e cient student learning process (18).…”
Section: Discussionmentioning
confidence: 99%
“…But this traditional model needs an expert in the post-simulation feedback session. Shifting the degree of primary learning responsibility from the expert to the learner through self-guided learning has received more attention in reducing resource intensity (17).…”
Section: Discussionmentioning
confidence: 99%